Rethinking the Third Mission of Ukrainian Universities in Wartime: Innovation, Social Resilience, and Postwar Reconstruction - Olena Orzhel; Olha Petroye; Alla Havryliuk; Olena Otych; Nataliia Shofolova (Bumi Publikasi Nusantara, 2026)
This study examines how the third mission of Ukrainian universities has transformed under wartime conditions and how it contributes to social resilience, innovation, and post-war reconstruction. The study used a qualitative comparative design based on 186 institutional documents from 30 Ukrainian universities. The analysis identified three interconnected dimensions of third-mission transformation: social responsibility and humanitarian support, innovation and regional development, and reconstruction-oriented engagement. The findings show that Ukrainian universities have expanded beyond teaching and research to become platforms for community support, knowledge mobilization, institutional cooperation, and recovery planning. The study contributes to third-mission scholarship by conceptualizing the university as a crisis-adaptive institution embedded in social and reconstruction processes.